2005
DOI: 10.1007/s00198-005-2025-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mass and bone turnover following tibial shaft fracture

Abstract: We conclude that: (1) bone loss following tibial shaft fracture occurs both proximal and distal to the fracture; (2) the decreased BMD is largest for trabecular bone in the tibia with similar measurements using DXA and pQCT; (3) there is limited recovery of bone lost at the hip and tibia at 1 year; (4) tibial speed of sound (SOS) demonstrated a greater decrease than calcaneal SOS when comparing z -scores; (5) BUA is the QUS variable that shows the biggest decrease of bone mass at the calcaneus; (6) increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 21 publications
6
117
1
8
Order By: Relevance
“…Furthermore, ALP activity is a marker of osteoblastic activity; that is, for bone turnover and bone remodeling. ALP level in serum increases during bone healing after fracture 28,29) . ALP functions in dentine mineralization and is retained as a marker of fully differentiated odontoblasts 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ALP activity is a marker of osteoblastic activity; that is, for bone turnover and bone remodeling. ALP level in serum increases during bone healing after fracture 28,29) . ALP functions in dentine mineralization and is retained as a marker of fully differentiated odontoblasts 27) .…”
Section: Discussionmentioning
confidence: 99%
“…The initial decrease in bone formation markers and the marked increase in ICTP immediately after fracture are mediated by immobilization and osteosynthesis after injury. Markers of bone turnover remain increased even after bone union is completed (11,(17)(18)(19). Background: Training of clinical pathologists is evolving and must now address the 6 core competencies described by the Accreditation Council for Graduate Medical Education (ACGME), which include patient care.…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Several investigators have suggested the type and location of a fracture might affect expression of bone markers during the fracture healing process, with bone markers in diaphyseal tibial fractures taking greater time to elevate than ankle [48,49] or distal radial fractures [25]. Nakagawa et al [31] also suggested that a larger bone surface and longer time to union might contribute to different degrees of bone marker changes.…”
Section: Discussionmentioning
confidence: 99%